Genetic Variability of the Colombian Collection of Lulo (Solanum quitoense Lam.) and Related Species of Section Lasiocarpa - Fory Sánchez, Paola Andrea; Sánchez Mosquera, I.; Bohórquez Cháux, Adriana; Ramírez, H.; Medina Cano, CI; Lobo Arias, Mario (2010)
An AFLP genetic variability study of the Colombian collection of lulo Solanum quitoense and related species of section Lasiocarpa was carried out. The aim was to elucidate the genetic polymorphism of such collection and interspecific affinities. Two primer combinations, E-ACG/M-CAT and E-ACG-M-CTC, were chosen out of 30 evaluated combinations based on their high expression levels of polymorphism. The UPGMA dendrogram, obtained through similarity analysis, exhibited systemic power with discrimination at species level and between the groups of Andean and Amazonian taxa from section Lasiocarpa, with a clear separation between Lasiocarpa species and outgroup taxa. Clustering patterns regarding the geographic origin of the accessions, as well as between materials of the S. quitoense botanical varieties septentrionale and quitoense were not evident. Wider genetic variability was observed in the wild section Lasiocarpa species than in the cultivated ones S. quitoense and S. sessiliflorum. The interespecific hybrids between S. hirtum and S. quitoense and backcrosses of these with S. quitoense exhibited greater variability in comparison to S. quitoense. The above, indicated the feasibility of the use of S. hirtum to broaden the genetic base of the cultivated species, with potentiality of S. psudolulo and S. vestissimum for the same purpose. The results obtained with the multiple analysis of correspondence were in agreement with those of the similarity index analysis, and the neighbor joining analysis with high “bootstrap” values, which indicates that the support of each cluster for the studied species is well represented.